2015
DOI: 10.1007/s11626-015-9915-x
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng stimulates alkaline phosphatase activity, collagen synthesis, and mineralization in osteoblastic MC3T3-E1 cells

Abstract: Total Panax notoginseng saponin (PNS) has been extensively used to treat a variety of diseases, such as bone fractures, soft tissue injuries, etc. In this study, mouse calvaria-original osteoblastic MC3T3-E1 cells were cultured in various concentrations of PNS (0.005-5 mg/mL) during the period (1, 5, 14, and 23 d). At the endpoint, the osteogenic capacity of MC3T3-E1 cells was investigated by measuring the alkaline phosphatase (ALP) activity, the deposited calcium, and the expression of osteogenic-related mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…ALP [ 30 ] is an early osteogenic marker and plays an important role in bone formation. A peak in ALP activity is indicative of differentiation [ 31 , 32 ]. We quantified ALP activity to evaluate the effect of quercetin on BMSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…ALP [ 30 ] is an early osteogenic marker and plays an important role in bone formation. A peak in ALP activity is indicative of differentiation [ 31 , 32 ]. We quantified ALP activity to evaluate the effect of quercetin on BMSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…PNS has previously been purported to exhibit pro-bone metabolism, neuroprotective, hepatoprotective, renoprotective, antitumor, cardioprotective, antidiabetic, and other beneficial effects, in addition to being safe and convenient to use [ 30 ]. Prior evidence also suggests that PNS and its main bioactive component, NGR1, can stimulate the proliferation, differentiation, and mineralization of osteoblasts through the enhancement of cellular ALP activity, ECM mineralization, and osteoblast-associated gene expression [ 31 , 32 ]. The results of the present study further confirmed that PNS administration was sufficient to enhance osteogenesis in a rabbit model of DO, with reductions in PPM1A expression together with the upregulation of TGF- β 1/Smad signaling pathway genes (T β R-II, SMAD2/3), potentially favoring osteogenic differentiation and DO regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that PN saponins promote osteogenesis, including proliferation, differentiation, and mineralization activity in osteoblasts. 77 Accordingly, NG-R1 significantly induces bone development by inhibition of RNAKL-mediated MAPK and NF-κB signaling pathways and suppression of osteoclastogenesis and bone resorption. 15 In addition, NG-R1 may significantly induce the expression of Runx-2 and Osx as well as the activity of ALP in MC3T3-E1 cells dose-dependently.…”
Section: Roles Of Ng-r1 In Bone Metabolism Regulationmentioning
confidence: 99%